The Artificial Mountain: a New Form of “Artialization” of Nature? - Claire Portal (Revue de Géographie Alpine)
Artificial mountains are artefacts, real or imaginary, whose identification is based on landscape models associated with natural mountains: whatever its origin, the mountain symbolizes duration and constitutes an unmovable and unchanging element. Following the social, cultural and technical evolutions, artificial mountains have attained new landscape values associated with the emergence of innovative concepts of the environment, particularly in urban areas. Having first been an ornamental element of urban parks, the artificial mountain has now become a full living space, at the heart of the reorganization of the post-industrial, vertical, green and recycled city. From a corpus of about forty realizations, real and imaginary, this paper studies how the designers of artificial mountains, mainly architects, are inspired by landscape models to introduce this mountainous nature into cities, but also how they are reinventing the idea of “the mountain”, by introducing new aesthetics and new features into renewed urban contexts.